Access to Expert Stroke Care with Telemedicine: REACH MUSC - Kazley, Abby S.; Wilkerson, Rebecca C.; Jauch, Edward C.; Adams, Robert J. (Frontiers in Neurology, 2012)
Stroke is a leading cause of death and disability, and rtPA can significantly reduce the long-term impact of acute ischemic stroke (AIS) if given within 3 hours of symptom onset. South Carolina is located in the stroke belt and has a high rate of stroke and stroke mortality. Many small rural SC hospitals do not maintain the expertise needed to treat AIS patients with rtPA. MUSC is an academic medical center using REACH MUSC telemedicine to deliver stroke care to 15 hospitals in the state, increasing the likelihood of timely treatment with rtPA. The purpose of this study is to determine the increase in access to rtPA through the use of telemedicine for AIS in the general population and in specific segments of the population based on age, gender, race, ethnicity, education, urban/rural residence, poverty, and stroke mortality. We used a retrospective cross-sectional design examining Census data from 2000 and Geographic Information Systems (GIS) analysis to identify South Carolina residents that live within 30 or 60 minutes of a Primary Stroke Center (PSC) or a REACH MUSC site. We include all South Carolina citizens in our analysis and specifically examine the population’s age, gender, race, ethnicity, education, urban/rural residence, poverty, and stroke mortality. Our sample includes 4,012,012 South Carolinians. The main measure is access to expert stroke care at a Primary Stroke Center (PSC) or a REACH MUSC hospital within 30 or 60 minutes. We find that without REACH MUSC, only 38% of the population has potential access to expert stroke care in SC within sixty minutes given that most PSCs will maintain expert stroke coverage. REACH MUSC allows 76% of the population to be within sixty minutes of expert stroke care, and 43% of the population to be within 30 minute drive time of expert stroke care. These increases in access are especially significant for groups that have faced disparities in care and high rates of AIS. The use of telemedicine can greatly